Clement and scriptural exegesis: the making of a commentarial theologian - Ward, H. Clifton (Oxford Early Christian Studies, 2022)
In a new treatment of the theological exegesis of Clement of Alexandria, this study suggests that an assessment of the reading practices that Clement employs from the grammatical and the memorial archives reveals his deep commitment to scriptural interpretation as the foundation of a theological imagination.